Vladas Jurgutis – the Economist, Politician, Pedagogue - Martišius, Stanislovas (Ekonomika, 1996)
Vladas Jurgutis (1885–1966) was a famous Lithuanian economist, an excellent pedagogue, and the ruler of the Lithuanian monetary policy during the years 1922–1929. The directions of his research are, the fiscal and monetary policy, the history of the national economy, the problems of the social economy policy, and the theory of the national economy. Vladas Jurgutis graduated from Munich University where historically new German economic ideas were dose to him. Vladas Jurgutis popularised Social Solidarity, the church’s social teaching. Though he had to live throught many life difficulties – Nazi imprisonment, Soviet Security persecution – Vladas Jurgutis managed to remain true to democratic and market economy ideals.